2021
DOI: 10.1007/s11056-020-09825-y
|View full text |Cite
|
Sign up to set email alerts
|

Drought resistance and gum yield performances in a Senegalia senegal (L.) Britton progeny trial in Senegal

Abstract: With continued global change as a result of land use changes, invasive species and changing climatic patterns, it is becoming increasingly important to understand the adaptability of Senegalia senegal provenances to maximize resilience in managed and natural populations of this species. The objective of this study is to investigate Senegalia senegal genotypic differences in water use efficiency (WUE) measured by stable 13C isotope composition in foliage according to their ploidy levels. Secondary objectives ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Variation among trees in their leaf morphological traits, including stomatal density and distribution, and epidermal features is of special interest in relation to climatic adaptation, because such traits may affect gas exchange and thereby plants' responses to key environmental factors such as light, atmospheric humidity, and CO 2 levels (Xu and Zhou 2008). It is known that leaf morphology can reflect environmental conditions (Halloy and Mark 1996;Traiser et al 2005;Royer et al 2008;Peppe et al 2011;Schmerler et al 2012;Koksheeva et al 2017), and link to drought adaptation (Abrams et al 1990). For example, plants in dry regions tend to have small leaves compared to plants from humid areas (McDonald et al 2003).…”
Section: Communicated By Gesslermentioning
confidence: 99%
See 2 more Smart Citations
“…Variation among trees in their leaf morphological traits, including stomatal density and distribution, and epidermal features is of special interest in relation to climatic adaptation, because such traits may affect gas exchange and thereby plants' responses to key environmental factors such as light, atmospheric humidity, and CO 2 levels (Xu and Zhou 2008). It is known that leaf morphology can reflect environmental conditions (Halloy and Mark 1996;Traiser et al 2005;Royer et al 2008;Peppe et al 2011;Schmerler et al 2012;Koksheeva et al 2017), and link to drought adaptation (Abrams et al 1990). For example, plants in dry regions tend to have small leaves compared to plants from humid areas (McDonald et al 2003).…”
Section: Communicated By Gesslermentioning
confidence: 99%
“…Diallo et al (2016) showed that polyploid seedlings grew faster than diploids under drought-stress conditions, suggesting that the existence of different ploidy levels in A. senegal can increase its potential to adapt to future climatic fluctuations in Africa. Recently, Sarr et al (2021) found that diploid and tetraploid populations differed in their foliar isotope ratios of carbon in a progeny trial in Senegal. However, only 15% of the variation in isotope composition was explained by the ploidy level, which suggests the existence of other factors affecting WUE in A. senegal.…”
Section: Communicated By Gesslermentioning
confidence: 99%
See 1 more Smart Citation
“…To optimize the restoration opportunities a model and scenarios should be identified to determine the feasible profitability and help in tracking progress. However, inevitably, many uncertainties affect key parameters concerning tree survival and growth, gum yield and price, all of which determine the profitability of this kind of restoration initiative (Mujawamariya & D'Haese 2012; Sarr et al 2021). Moreover, the model should be tested and approved first in a pilot area of at least 2,000 ha (Beatty et al 2018).…”
Section: Overview Of Large‐scale Plantation Programs Undertaken In Th...mentioning
confidence: 99%
“…Knowledge of genetic resources of important sahelian tree species as well as their ability to adapt to drought conditions is crucial for sustainability of plantations/restoration initiatives and would increase benefits for local people. For instance, recent outputs based on research revealed promising S. senegal diploid and tetraploid trees as good sources for the diffusion of increased gum yield production and well drought‐adapted planting material in the Senegalese Sahel for future ecosystem restoration works (Diallo et al 2015, 2016; Sarr et al 2021). These results might be a good starting point to develop management tools for species conservation and economic incentives to sustain ecological resilience.…”
Section: Issues and Challengesmentioning
confidence: 99%